2016
DOI: 10.1111/codi.13330
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and success rates of perineal procedures for fistula‐in‐ano: a systematic review

Abstract: Success and adoption rates tend to decrease with time. Differences in patient selection, duration of follow-up, length of availability of the individual procedure and heterogeneity of treatment protocols contribute to the diverse results in the literature. Differences in success rates over time were evident, suggesting that both international trials and global best practice consensus are desirable. Further prospective randomized controlled trials with homogeneity and clear objective parameters would be needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 109 publications
1
57
1
3
Order By: Relevance
“…Kontovounisios C et al [22] reported 759 cases of ligation of intersphincteric fistula tract (LIFT) and found the success rate of LIFT to be 51-94%, which was not suitable for the treatment of complex anal fistulas. In conclusion, the above methods still have some shortcomings, such as low cure rate, long healing time, or high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Kontovounisios C et al [22] reported 759 cases of ligation of intersphincteric fistula tract (LIFT) and found the success rate of LIFT to be 51-94%, which was not suitable for the treatment of complex anal fistulas. In conclusion, the above methods still have some shortcomings, such as low cure rate, long healing time, or high recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study is weakened by a relatively long inclusion period and a degree of loss to follow‐up. In a recent systematic review of adoption and success rates of perineal procedures for fistula in ano , it was found that the duration (recruitment phase) of each study influenced the success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the advancement flap has been used as an alternative approach; this involves closure of the internal opening of a high fistula, combined with coring out of the tract, avoiding division of the sphincter itself. In recent years, several additional sphincter‐preserving techniques have been developed in further attempts to minimize sphincter damage and improve functional outcome, including fibrin glue sealing, ligation of the fistula tract and use of collagen plugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Der transperineale Zugang bei der rektovaginalen Fistel war diesbezüglich in den 1990er-Jahren verbreitet und zeigte vielversprechende Ergebnisse [23,24]. Auch in aktuellen Studien lässt sich eine "Renaissance" des transperinealen Zugangs beobachten [26]. Darüber hinaus sind die eigenen Erfahrungen beeindruckt von den Ergebnissen der "LIFT-Methode" bei komplexen Analfisteln kryptoglandulärer Genese [27 -30].…”
Section: Diskussionunclassified